The axiological dimension in psychiatric diagnosis - Lolas Stepke, Fernando (Acta Bioethica, 2009)
This paper addresses the need to consider the valoric constitution of patients and therapists in the context of psychiatric encounters and proposes the notion of axiogram, a depiction of values and moral beliefs to incorporate into the clinical history as a proxy to a nosological dimension complementing the traditional multiaxial approach.